2019
DOI: 10.1108/afr-02-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the intention to use commodity futures contracts

Abstract: Purpose Adoption rates of commodity futures contracts among farmers are rather low in Europe despite their political support. The purpose of this paper is to examine whether the Technology Acceptance Model (TAM) can contribute to the understanding of farmers’ intention to use commodity futures contracts. Here, the authors explicitly distinguish between usage motives for price risk reduction and speculation. Design/methodology/approach The study is based on an online survey with 134 German farmers using parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…Th ese results indicate that farmers have appropriate expectations of the instrument. Th is is not self-evident, as research has shown that European farmers' sometimes expect fi nancial derivatives to enhance prices rather than stabilise them (Bergfj ord 2007;Michels et al 2019).…”
Section: Case Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th ese results indicate that farmers have appropriate expectations of the instrument. Th is is not self-evident, as research has shown that European farmers' sometimes expect fi nancial derivatives to enhance prices rather than stabilise them (Bergfj ord 2007;Michels et al 2019).…”
Section: Case Descriptionmentioning
confidence: 99%
“…As agriculture is a risky business, policymakers and advisors have been advocating and stimulating the use of risk management instruments. Th is has particularly been the case in Europe, following the Common Agricultural Policy's shift from managed to unmanaged markets over the last decades (Veerman et al 2016;Michels et al 2019). One of the advocated solutions for managing price risk is the use of fi nancial derivatives, which allow farmers to manage risk without interfering with production choices and marketing channels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are defined as “either verbal or written agreements between a buyer and a producer that set a price and/or an outlet for a commodity before harvest or before the commodity is ready to be marketed” (Harwood et al., 1999). Despite their increasing relevance, marketing contracts are not widely used (Pannell et al., 2008; Simmons, 2002), particularly in Europe (Michels et al., 2019). Using an original dataset, we propose here to identify factors influencing the adoption of marketing contracts by French farmers, with a specific focus on the hedging (price risk management) and the price‐enhancement components.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Michels et al. (2019) show that farmers’ intention to use futures contracts is mostly driven by their belief that commodity futures contracts can enhance received prices rather than price risk reduction.…”
Section: Introductionmentioning
confidence: 99%